2016
DOI: 10.1007/s10964-016-0554-7
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Perspectives on Parent–Adolescent Discrepancies: Existing Findings and Future Directions

Abstract: As summarized in this commentary, the first generation of cross-informant agreement research focused on perceptions of child and adolescent mental health. Contributions of this research include demonstrating that modest cross-informant agreement is a very robust phenomenon, utilizing numerous statistical approaches to measure degree of agreement, and identifying many factors that moderate agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Such findings corroborate the study by Youngstrom et al (2000), which indicated that adolescents perceive themselves as having more internalizing and externalizing symptoms than their teachers. It should be pointed out that as the sample considered refers to students who were not in psychological or psychiatric care, the results also confirm that adolescents highlight more behavior problems than their relatives and teachers, unlike those referred to mental health services, whose evaluation of adults is primarily considered (Chen et al, 2017;Rescorla, 2016;Rocha et al, 2011;Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Such findings corroborate the study by Youngstrom et al (2000), which indicated that adolescents perceive themselves as having more internalizing and externalizing symptoms than their teachers. It should be pointed out that as the sample considered refers to students who were not in psychological or psychiatric care, the results also confirm that adolescents highlight more behavior problems than their relatives and teachers, unlike those referred to mental health services, whose evaluation of adults is primarily considered (Chen et al, 2017;Rescorla, 2016;Rocha et al, 2011;Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…In view of the foregoing, it is noted that disagreements between adolescents, family members and teachers need to be taken as fact, since the informants considered are inserted in different contexts and cannot be omitted in the interpretation of information when evaluating adolescents for clinical or of research (Gomez et al, 2014;Grigorenko et al, 2010). In addition, studies have pointed out that discrepancies between informants have their value insofar as they indicate looking at the characteristics and demands of each evaluator and should not be understood as a measurement error that requires a methodological resolution (De Los Reyes, Thomas, Goodman, & Kundey, 2013;Rescorla, 2016). However, there is a need for further research that addresses this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This information could help to get more insight in the interplay of life circumstances and external assessment of trauma symptoms in the long-term aftermath of disasters. Consequently, future research comparing informants’ perceptions of family functioning should be the focus of parent-child agreement because family functioning is assumed to explain cross-informant discrepancies in different cultures [54].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a meta-analysis (De Los Reyes et al, 2019b ) revealed that congruence is related to cultural characteristics. Moreover, as Rescorla ( 2016 ) underlined, there is a need for cross-cultural direct comparisons regarding parent–child discrepancies. Very few studies directly compared parent–child discrepancy across nations, and the ones that did, as for example Rescorla et al ( 2013 ), did not test cross-cultural measurement invariance.…”
Section: Introductionmentioning
confidence: 99%